2020
DOI: 10.1007/s00066-020-01697-7
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating dose–volume histogram parameters of swallowing organs at risk in a videofluoroscopy-based predictive model of radiation-induced dysphagia after head and neck cancer intensity-modulated radiation therapy

Abstract: Purpose To develop a videofluoroscopy-based predictive model of radiation-induced dysphagia (RID) by incorporating DVH parameters of swallowing organs at risk (SWOARs) in a machine learning analysis. Methods Videofluoroscopy (VF) was performed to assess the penetration-aspiration score (P/A) at baseline and at 6 and 12 months after RT. An RID predictive model was developed using dose to nine SWOARs and P/A-VF data at 6 and 12 months after treatment. A total of 72 dosimetric features for each patient were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…After parameter optimization and ten rounds of cross-validation, the best prediction ability was achieved by RF, with an AUC of 0.827. In a previous study Jamie et al used penalised logistic regression (PLR), support vector classi cation (SVC) and random forest classi cation (RFC) algorithms to predict the model of mucositis caused by head and neck radiotherapy, which was cross-validated for 100 iterations [15]. Their results showed that the RFC standard, which does not contain spatial information, had the best accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…After parameter optimization and ten rounds of cross-validation, the best prediction ability was achieved by RF, with an AUC of 0.827. In a previous study Jamie et al used penalised logistic regression (PLR), support vector classi cation (SVC) and random forest classi cation (RFC) algorithms to predict the model of mucositis caused by head and neck radiotherapy, which was cross-validated for 100 iterations [15]. Their results showed that the RFC standard, which does not contain spatial information, had the best accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a statistically significant association between the presence of this tumor subsite and variations of all but one (F-score) MDADI scale and subscale scores from baseline to 12 months after RT. It is noteworthy that, in a recent mono-institutional experience [ 28 ], the base of tongue has been identified as one of the most crucial SWOARs whose damage has been ranked of highest priority in the occurrence of post-deglutition inhalation. In this regard, a possible explanation of our findings might be the reduction of the posterior propulsive driving force of the base of tongue, due to the pre-treatment tumor infiltration of its musculature as well as to post-treatment fibrotic radiation damage, causing patients to perceive deglutition disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, novel ML models to predict toxicities following radiation therapy (RT) have been developed ] conducted a systematic review summarizing ML models developed to predict HNC treatment toxicities following RT, including many that affect deglutitive function. Among the 28 studies reviewed, xerostomia [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] was the most frequently investigated endpoint, followed by swallowing dysfunction [28][29][30], weight loss and placement of a gastrostomy tube [31,32 & ]. Most studies applied supervised learning modalities (models that rely on labeled input and output training data) including logistic regression (LR), multivariable LR, and penalized LR [11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], while only few reported reinforcement learning models [14, 18,32 & ], such as multilayer perceptron and convolutional neural networks (CNN).…”
Section: Machine Learning Applications To Predict and Prevent Voice A...mentioning
confidence: 99%
“…Among the 28 studies reviewed, xerostomia [11–27] was the most frequently investigated endpoint, followed by swallowing dysfunction [28–30], weight loss and placement of a gastrostomy tube [31,32 ▪ ]. Most studies applied supervised learning modalities (models that rely on labeled input and output training data) including logistic regression (LR), multivariable LR, and penalized LR [11–13,15–31], while only few reported reinforcement learning models [14,18,32 ▪ ], such as multilayer perceptron and convolutional neural networks (CNN).…”
Section: Machine Learning Applications To Predict and Prevent Voice A...mentioning
confidence: 99%
See 1 more Smart Citation